Class, parenting and academic stress in Norway: middle-class youth on parental pressure and mental health. Issue 4 (4th July 2021) - Eriksen, Ingunn Marie
ABSTRACT: Mental health problems among young people have increased in recent decades, particularly among middle-class youth, a development often related to increasing achievement pressure. This paper explores how young people from the financial and cultural middle classes in Norway experience school stress and their parents' values and practices concerning school achievement. Based on interviews with 53 boys and girls, aged 15–17, the study identifies 2 narratives. The first narrative is told by youth from the financial middle classes. They talk about their parents' explicit demands, and tie the parental pressure to their achievement-related mental health problems. The second narrative describes a ceaseless self-drive, told by youth mainly from the cultural middle class. They portray their parents' expectations as implicit rather than explicit, and they see mental health problems as achievement related – but not related to their parents. In both narratives, however, self-worth relies on achievement.